Simultaneous Quantification and Pharmacokinetic Characterization of Doxapram and 2-Ketodoxapram in Porcine Plasma and Brain Tissue - Manuel Kraft; Kathrin I. Foerster; Felix Wiedmann; Max Sauter; Amelie Paasche; Pablo L. Blochberger; Baran Yesilgöz; Yannick L'hoste; Norbert Frey; Walter E. Haefeli; Jürgen Burhenne; Constanze Schmidt (MDPI AG, 2022)
Atrial fibrillation (AF) is an arrhythmia associated with an increased stroke risk and mortality rate. Current treatment options leave unmet needs in AF therapy. Recently, doxapram has been introduced as a possible new option for AF treatment in a porcine animal model. To better understand its pharmacokinetics, three German Landrace pigs were treated with intravenous doxapram (1 mg/kg). Plasma and brain tissue samples were collected. For the analysis of these samples, an ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) assay for the simultaneous measurement of doxapram and its active metabolite 2-ketodoxapram was developed and validated. The assay had a lower limit of quantification (LLOQ) of 10 pg/mL for plasma and 1 pg/sample for brain tissue. In pigs, doxapram pharmacokinetics were biphasic with a terminal elimination half-life (t1/2) of 1.38 ± 0.22 h and a maximal plasma concentration (cmax) of 1780 ± 275 ng/mL. Its active metabolite 2-ketodoxapram had a t1/2 of 2.42 ± 0.04 h and cmax of 32.3 ± 5.5 h after administration of doxapram. Protein binding was 95.5 ± 0.9% for doxapram and 98.4 ± 0.3% for 2-ketodoxapram with a brain-to-plasma ratio of 0.58 ± 0.24 for doxapram and 0.12 ± 0.02 for 2-ketodoxapram. In conclusion, the developed assay was successfully applied to the creation of pharmacokinetic data for doxapram, possibly improving the safety of its usage.